From Hot Cakes to Cold Feet: A Contingent Perspective on the Relationship between Market Uncertainty and Status Homophily in the Formation of Alliances. (16th October 2013) - Collet, Francois; Philippe, Déborah
Abstract In this study, we reconsider the classical positive association between the level of market uncertainty and an organization's propensity to form ties with organizations of similar status. Although prior research argues that the greater the uncertainty, the higher the level of status homophily, we suggest that this relationship is contingent upon framing that affects positive or negative valence towards uncertainty. In an up market, organizations tend to frame uncertainty as upside risk, and thus will subsequently favour explorative uncertainty‐mitigation devices; whereas, in a down market, organizations primarily frame uncertainty as downward risk, and thus will rely on more conservative uncertainty‐mitigation mechanisms. We therefore predict that a greater number of status‐heterophilous ties will be formed in an up market than in a down market. We discuss the implications of our results for status theory and more broadly for research on strategic decision making under uncertainty.